Impact of physical function impairment and multimorbidity on mortality among community-living older persons with sarcopaenia: results from the ilSIRENTE prospective cohort study. Issue 7 (25th July 2016) - Landi, Francesco; Calvani, Riccardo; Tosato, Matteo; Martone, Anna Maria; Bernabei, Roberto; Onder, Graziano; Marzetti, Emanuele
Abstract : Objective: Sarcopaenia and physical function impairment may have a greater effect on survival than other clinical characteristics, including multimorbidity. In this study, we evaluated the impact of sarcopaenia on all-cause mortality and the interaction among muscle loss, physical function impairment and multimorbidity on mortality risk over 10 years in older community-dwellers. Design: Prospective cohort study. Setting: Population-based study. Participants: All persons aged 80+ years living in the community in the Sirente geographic area (L'Aquila, Italy) (n=364). Participants were categorised in the sarcopaenic or non-sarcopaenic group based on the European Working Group on Sarcopenia in Older People criteria. Primary and secondary outcome measures: (1) All-cause mortality over 10 years according to the presence of sarcopaenia and (2) impact of physical function impairment, assessed using the Short Physical Performance Battery (SPPB), and multimorbidity on 10-year mortality risk in persons with sarcopaenia. Results: Sarcopaenia was identified in 103 participants (29.1%). A total of 253 deaths were recorded over 10 years: 90 among sarcopaenic participants (87.4%) and 162 among non-sarcopaenic persons (65.1%; p<0.001). Participants with sarcopaenia had a higher risk of death than those without sarcopaenia (HR=2.15; 95% CI 1.02 to 4.54). When examining the effect of sarcopaenia and physical function impairment on mortality, participants with low physical performance levels showed greater mortality. Conversely, the mortality risk was unaffected by multimorbidity. Conclusions: Our findings show that physical function impairment, but not multimorbidity, is predictive of mortality in older community-dwellers with sarcopaenia. Hence, in sarcopaenic older persons, interventions against functional decline may be more effective at preventing or postponing negative health outcomes than those targeting multimorbidity.